Pengetahuan Masyarakat Desa Doy Kecamatan Ulee Kareng Kota Banda Aceh tentang Obat Tradisional - Ceriana, Ria; Verawati; Masykur (Jurnal Mitra Pengabdian Farmasi, 2023)
Community service aims to help improve knowledge, skills and public health. This service is carried out to find out and increase the knowledge of the people of Doy Village, Ulee Kareng District, Banda Aceh City regarding traditional medicine. Traditional medicine has been used by people for generations to treat various diseases. This community service was held in June 2022 in Doy Village, Ulee Kareng District, Banda Aceh City, attended by around 20 participants. This activity uses a lecture and counseling model accompanied by a questionnaire instrument to see the level of public knowledge about traditional medicine. The results of this activity are known that the community is 100% about knowing and using traditional medicine. However, about 80% of those who have just planted TOGA plants in their yards. Then after the service was carried out by means of counseling, there was an increase in public knowledge to 100%. Based on this activity it is known that there are about 17 types of plants used by the people of Doy Village as traditional medicine.